Analisis Pelaksanaan Uji Kompetensi Jabatan Fungsional Kesehatan Di Dinas Kesehatan Provinsi Sumatera Selatan - Astuti, Nerry Yudi; Sulastri, Sri; Zuber, Konar (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
In the study entitled Implementation of Health Functional Level Tests at the South Sumatra District Health Office, it was found that the test takers did not understand how to evaluate competency tests and the test takers did not fully understand the functional points. from the test. portfolio evaluation. such as control, task control. This study used a qualitative descriptive method which was analyzed in several stages, namely. summarize, present, conclude and check with the South Sumatra Provincial Health Office. Information was collected through literature study, observation and interviews. Data abstraction control techniques are carried out by extending the time of participation, constancy of observation, triangulation and peer review, and making references. This study uses the theory of Terry (2006) which looks at four factors, namely: planning, organizing, implementing and controlling. Based on the results of the research, it is known that planning: Implementation of functional competency tests was not optimally successful, even though it was supported by management of the employee development budget in implementing functional work ability tests. Organization: The structure and division of labor for the implementation of functional job qualification tests are not running optimally. Implementation: in accordance with the budget plan made at the time of budget execution. Monitoring: does not run optimally because the legal basis for task guidance is incomplete.